AN EFFECTIVE STUDY AND ANALYZE OF THE KNOWLEDGE MANAGEMENT EFFECT ON EDUCATIONAL SERVICES QUALITY-A FIELD STUDY ON THE AL-IRAQIA UNIVERSITY - POSTGRADUATE STUDIES DEPARTMENT - M.M. Najah Madad Werdee Kazim (Scholars Digest Publishing, 2024)
Knowledge management is one of the basic pillars on which human resources are based, especially in academic institutions. Many researches and studies have been reviewed that are related to knowledge management in academic institutions around the world. Therefore, this article was written with the aim of studying and analyzing knowledge management and the main effect(s) on educational service(s) quality at Al-Iraqia University, Postgraduate Studies Department. In this study, there are six dimensions for knowledge management as follow: knowledge generation, storage, and distribution. Also, quality of educational services. The study community in this article included 40 faculty members at the university - Postgraduate Studies Department. An effective questionnaire is prepared and then it is distributed to the sample members. The number of returned-back questionnaires was 30. For analytical and statistical purposes, the descriptive analytical approach was used with the help of the Statistical Package for Social Sciences (SPSS) program to derive results. These results showed that there is a very clear moral effect with statistical significance, especially in knowledge management and its dimensions. This article also provides some interest recommendations, also adopting plans to develop and highlight the skills and capabilities of faculty members, as well as increasing interest in the quality of educational services by offering student support services by activating the Academic Guidance Committee for Students as well as the Student Activities Committee.
Keywords: Knowledge Management, Quality of Educational Services, SPSS, Human Resources.